Randomized phase II study of two intercalated combinations of eribulin mesylate and erlotinib in patients with reviously treated advanced non-small-cell lung cancer - Tony S. Mok (2018)
Background: This phase II, open-label study investigated intercalated combinations of eribulin and erlotinib in unselected patients with advanced non-small-cell lung cancer previously treated with platinum-based chemotherapies. Patients and methods: Eligible patients were randomized to eribulin mesylate 2.0 mg/m 2 on day 1 with erlotinib 150 mg on days 2-16 (21-day regimen) or eribulin mesylate 1.4 mg/m 2 on days 1 and 8 with erlotinib 150 mg on days 15-28 (28-day regimen). The primary end point was objective response rate (ORR). Results: One hundred and twenty-three patients received ≥1 cycle of therapy (63, 21-day regimen; 60, 28-day regimen). ORRs were 13% [95% confidence interval (CI) 6%-24%] and 17% (95% CI 8%-29%), and disease control rates were 48% (95% CI 35%-61%) and 63% (95% CI 50%-75%) for the 21- and 28-day regimens, respectively. The median progression-free survival and overall survival were similar with both regimens. Both regimens were well tolerated with common grade ≥3 toxicities being neutropenia, asthenia/fatigue, and dyspnoea. Sequential administration of erlotinib did not interfere with the pharmacokinetic profile of eribulin. Conclusion: Intercalated combination of eribulin and erlotinib demonstrated modest activity and the addition of erlotinib did not appear to improve treatment outcome in an unselected population. The 28-day regimen is suitable for further investigation. © The Author 2014. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.